Application of shell-cluster comprehensive model to α resonant scattering - Maeda Taiki; Nakamoto Riu; Fumimoto Toshihiro; Ito Makoto (EPJ Web of Conferences)
We apply the comprehensive model of the shell model and the cluster model to the α + 16O resonant scattering. In this model, the coupling of the shell model configuration with 16O + four nucleons and the cluster model configuration with 16O + α is explicitly solved. The absorbing boundary condition is imposed on the α + 16O cluster configuration, and the excitation function of the elastic scattering is calculated from the method of the continuum level density. The shell + cluster calculation nicely reproduces the sharp resonant structures with a small energy interval appearing in the excitation function although the α cluster model reproduces only the broad and gross structure in the excitation function. The resonance width generated by the coupling with the shell model configuration is discussed in comparison to the experimental width.